2011
DOI: 10.1155/2011/868632
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Reliability of Anatomic Landmarks in Safe Lumbar Puncture Using Magnetic Resonance Imaging: Does Sex Matter?

Abstract: Aim. To determine the level of the conus medullaris-Tuffier's line, and conus medullaris-Tuffier's line distance using imaging and evaluate their relation to age and gender. Methods. We performed a cross-sectional study of 189 adult participants, who underwent MR imaging of lumbosacral spine. Each vertebra was divided into 3 equal segments (upper, middle, and lower), and intervertebral disc space was also assumed as one segment. All segments from T12 upper segment to L5S1 intervertebral disc were numbered con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 18 publications
(19 reference statements)
2
7
0
1
Order By: Relevance
“…These results are consistent with those of a study of 145 neonates using ultrasound; it reported that the termination of the spinal cord was at a median level of L2 (12). A recent study demonstrated a lower level of conus medullaris in women, especially in elderly women (13). However, there was no difference between male and female in our study group.…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with those of a study of 145 neonates using ultrasound; it reported that the termination of the spinal cord was at a median level of L2 (12). A recent study demonstrated a lower level of conus medullaris in women, especially in elderly women (13). However, there was no difference between male and female in our study group.…”
Section: Discussionsupporting
confidence: 93%
“…Perhaps this has been the inspiration for many studies however despite being more studies are conducted in the adult population, studies in the pediatric age group are not sufficiently available. MR imaging studies demonstrated that the Tuffier's line were in a significantly lower position in females compared to males in adults [4,8]. A similar result demonstrated by Windisch et al in a cadaveric study [9].…”
Section: Discussionsupporting
confidence: 56%
“…Most cadaveric studies show variability in CM position but it most commonly terminates at L1-L2 in adults (Saifuddin et al, 1998). Other studies demonstrate that the CM position is rarely below L2-L3 in normal cases (Tubbs and Oakes, 2004;Rahmani et al, 2011). Previous studies in supine patients using midsagittal lumbar spine magnetic resonance imaging (MRI) revealed the average CM termination position at the lower third of the L1 vertebral body, with a range from mid T12 to upper L3 (Boon et al, 2004).…”
Section: Introductionmentioning
confidence: 99%